Thermochemical oscillation of methane MILD combustion diluted with N2/CO2/H2O. Issue 1 (2nd January 2019) - Bagheri, Ghobad; Lavadera, Marco Lubrano; Ranzi, Eliseo; Pelucchi, Matteo; Sabia, Pino; de Joannon, Mariarosaria; Parente, Alessandro; Faravelli, Tiziano
ABSTRACT: Strict environmental rules endorse moderate or intense low oxygen dilution (MILD) combustion as a promising technology to increase efficiency while reducing pollutants emission. The experimental and theoretical investigation of oscillatory behaviours in methane MILD combustion is of interest to prevent undesired unstable combustion regimes. In this study new speciation measurements were obtained in a jet-stirred flow reactor (JSR) for stoichiometric mixtures of CH4 and O2, diluted in N2, CO2 and N2 -H2 O, at p = 1.1 atm and T = 720–1200 K. Oscillations were experimentally detected under specific temperature ranges, where system reactivity is sufficient to promote ignition, but not high enough to sustain complete methane conversion. A thorough kinetic discussion highlights reasons for the observed phenomena, mostly focusing on the effects of different dilutions.